RESPON PERTUMBUHAN KAYU PUTIH (Melaleuca cajaputi) TERHADAP PEMBERIAN MEDIA PUPUK HAYATI ECOFERT - Faisal Anwar; Eny Dwi Pujawati; Adistina Fitriani (Universitas Lambung Mangkurat, 2023)
Cajuput has the advantage of being able to grow in dry to wet soil. Cajuput plant is one of the producers of essential oils that are used as ingredients for health or pharmaceutical products. One of the essential oil needs for eucalyptus oil is still lacking in production. Therefore it is necessary to have a certain treatment so that the growth of eucalyptus can be even better. The purpose of this study was to analyze the effect of eucalyptus growth based on live percentage parameters, height growth parameters, diameter and shoots with the application of Ecofert biofertilizer. This research method was carried out using a completely randomized design (CRD) which consisted of 5 different treatments, namely 1) treatment A without the application of Ecofert biofertilizer; 2) treatment B application of 10 grams of Ecofert fertilizer; 3) treatment C with 20 grams of Ecofert fertilizer; 4) treatment D application of 30 grams of Ecofert fertilizer; 4) treatment E was the application of 40 grams of Ecofert fertilizer. From each treatment, the observation of the percentage of life got a range of 90%-100%, the highest result at the end of the observation of the average height increase in the E 40 grams treatment was 32.445 cm, the average increase in diameter in the E 40 grams treatment was 3.83 mm, and the growth of shoots with the highest value in treatment E was 20.9 shootsKayu putih memiliki kelebihan bisa tumbuh di tanah kering hingga basah. Tanaman kayu putih salah satu penghasil minyak atsiri yang digunakan sebagai bahan produk kesehatan atau farmasi. Kebutuhan minyak atsiri salah satunya untuk minyak kayu putih masih kekurangan produksinya. Maka dari itu perlu adanya perlakuan tertentu agar pertumbuhan kayu putih bisa lebih baik lagi. Tujuan penelitian ini untuk menganalisis pengaruh pertumbuhan tanaman kayu putih bedasarkan parameter persentase hidup, parameter pertambahan tinggi, diameter dan tunas dengan pemberian pupuk hayati Ecofert. Metode penelitian ini dilakukan dengan Rancangan Acak Lengkap (RAL) yang terdiri dari 5 perlakuan berbeda yaitu 1) perlakuan A tanpa pemberian pupuk hayati Ecofert; 2) perlakuan B pemberian pupuk Ecofert 10 gram; 3) perlakuan C pemberian pupuk Ecofert 20 gram; 4) perlakuan D pemberian pupuk Ecofert 30 gram; 4) perlakuan E pemberian pupuk Ecofert 40 gram. Dari setiap perlakuan pengamatan dari persentasi hidup mendapatkan kisaran 90%-100%, hasil tertinggi diakhir pengamatan dari rata-rata pertambahan tinggi pada perlakuan E 40 gram mendapatkan 32,445 cm, pada pertambahan rata-rata pertambahan diameter diperlakuan E 40 gram sebesar 3,83 mm, dan pertambahan tunas dengan nilai tertinggi pada perlakuan E sebesar 20,9 satuan tunas